Perceived Parental Functioning, Self-Esteem, and Psychological Distress in Adults Whose Parents are Separated/Divorced - Verrocchio, Maria C.; Marchetti, Daniela; Fulcheri, Mario (Frontiers in Psychology, 2015)
Objective. The objective of this research was to identify retrospectively the alienating behaviors and the parental bonding that occurred in an Italian sample of adults whose had parents separated or divorced and their associations with self-esteem and psychological distress. Methods. Four hundred seventy adults in Chieti, Italy, completed an anonymous and confidential survey regarding their childhood exposure to parental alienating behaviors (using the Baker Strategy Questionnaire), quality of the parent-child relationship (using Parental Bonding Instruments), self-esteem (using Rosenberg Self-Esteem Scale), and global psychological distress (using Global Severity Index of Symptom Checklist-90-Revised). Results. About 80% of the sample reported some exposure to parental alienating behaviors; about 65-70% of the sample has perceived non optimal parenting by mother and by father; individuals who experienced affectionless control (low care and high overprotection) reported significantly higher exposure to parental loyalty conflict behaviors. Overall rates of reported exposure to low care, and overprotection and parental loyalty conflict behaviors were statistically significantly associated with self-esteem as well as the measure of current psychological distress. Results revealed that exposure to parental loyalty conflict behaviors and self-esteem were associated with psychological distress over and above the effects of parental bonding and age. Conclusions. The pattern of findings supports the theory that children exposed to dysfunctional parenting, and with low self-esteem are at risk for their long-term psychological functioning. Implications for health policy changes and strengthening social services are discussed.